Public Service by the Government of Papua Province in the Special Autonomy - Efraim Kambu (Journal of Social and Development Sciences, 2016)
Special Autonomy assigns its rights and obligations to local governments to regulate and manage their own affairs and interests of the society so that people increasingly can be served well. But in fact, public services provided is not maximized. This study used qualitative methods, data sources are divided into two types of data sources, namely primary and secondary data sources. The results of this study indicate that there is still lack of public services the Government of Papua Province visible from the weak aspects of responsiveness, which local governments less responsive to some of the problems in the field of education, economy and industry growth and physical development as well as non-physical. From the aspect of responsibility is also still found their weaknesses, which the Government of Papua Province is still not fully overcome the problems of corruption and poverty. Meanwhile, from the aspect of accountability, it is known that the performance of governance in Papua in providing public services are not running optimally, one reason is the lack of competence and capability of local government officials.